Pengaruh Budaya Organisasi terhadap Kualitas Pelayanan Kesehatan : Tinjauan Literatur - Mauriska Nara Sandi; Uci Intan Permatasari; Purwadhi; Yani Restiani Widjaja (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Organizational culture is one of the key factors that influence the quality of healthcare. A positive organizational culture has been shown to support patient satisfaction, higher efficiency, and overall patient health outcomes. The method used in this study is a literature review, which aims to collect and analyze various sources relevant to the topic discussed. In a recent literature review on the influence of organizational culture on healthcare quality, a number of studies have shown that a positive organizational culture contributes significantly to improved service quality. Data shows that hospitals that implement strong cultural values such as empathy and professionalism experience a 20% increase in patient satisfaction compared to hospitals that have a weak organizational culture. Some practical recommendations for managing organizational culture in healthcare institutions include it is important for management to actively identify and develop cultural values that support service quality, healthcare institutions need to create effective communication channels to listen to feedback from employees and patients, healthcare institutions should also pay attention to employee welfare as part of organizational culture, it is important for healthcare institutions to conduct periodic evaluations and measurements of organizational culture and its impact on service quality. Finally, collaboration with external stakeholders, such as educational institutions and communities, can enrich the organizational culture in healthcare institutions.